Symbolic Literacy and Sharia Pseudo-Inclusion: A Paradoxical Analysis and TSR-Maqasid Strategy in Indonesia - Istianingsih, Istianingsih; Adiandari, Ade Maharini; Arafah, Willy; Doktoralina, Caturida Meiwanto; Nugroho, Lucky (Baca Dulu Publisher, 2025)
This research is motivated by the phenomenon of a significant gap between the literacy index and Islamic financial inclusion in Indonesia, as well as the fraud case of PT Dana Sharia Indonesia (DSI) in 2026 which reveals the practice of